Hop to It: The First Animal Model of Autoimmune Postural Orthostatic Tachycardia Syndrome - Amanda J. Miller; Taylor A. Doherty (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
See Article Li et al